Anemia in Inflammatory Bowel Disease: An Under-Estimated Problem? - Rogler, Gerhard; Vavricka, Stephan (Frontiers in Medicine, 2015)
Anemia is one of the most frequent complications and/or extraintestinal manifestations of inflammatory bowel disease (IBD). Iron deficiency is the most important cause of anemia in Crohn’s disease and ulcerative colitis patients. Iron deficiency even without anemia may impact the quality of life of our IBD patients. In the last ten years the understanding of the pathophysiology of iron deficiency anemia and “anemia of chronic diseases” has increased, new diagnostic tools have been developed and new therapeutic strategies have been discussed. Hepcidin has been identified to be a central regulator of iron absorption from the intestine and of iron plasma levels. Hepcidin is regulated by iron deficiency but also as an acute phase protein by pro-inflammatory mediators such as interleukin-6. Innovative diagnostic tools with respect to iron metabolism have not been introduced in clinical routine or are not available for routine diagnostics. As iron substitution therapy is easy these days with a preference for intravenous substitution the impact of differential diagnosis of anemia in IBD patients is underestimated.